Analysis of leadership and educational quality in the technical vocational institutes of Yamasá, Dominican Republic (Revista Investigación & praxis en CS Sociales, 2023)
In the Dominican Republic, educational quality is a priority issue, and therefore, numerous efforts have been made to improve it. However, there are still challenges to be faced to ensure high-quality education for all students. The research we present aims to understand how the functioning, style, and performance of leadership in Dominican schools relate to the quality of educational processes. This study is a derivation of an ongoing doctoral thesis focusing on leadership and educational quality. It seeks to determine possible connections between educational quality and the predominant leadership styles in educational centers in the Dominican Republic. For the purpose of this study, we will focus on educational centers in district 17-01 of Yamasá, in the province of Monte Plata. We have decided to base ourselves on the state of the art of this doctoral thesis since it is still in the process of being developed. In doing so, we aim to contribute to the body of knowledge surrounding school leadership and its impact on educational quality in the Dominican Republic, particularly in technical vocational schools.
Keywords: Leadership; educational quality; state of the art.